The Global Political Economy of the Environment and Tourism - Kütting, G. author. aut Link
X, 193 p.
Keywords: This book examines how local and global environment-society relations play out in coastal communities dependent on tourism for economic survival. It analyzes the consequences of social and economic policies on remote areas and makes a case for studying the role of environmental values in global environmental governance.